A Review: Method of Preparing Palm Oil Based Polyurethane - Syarifah Norsuhaila, Syed Mahmud; Mohamad Ashry, Jusoh; Salleh Eesaa, Jasim (Universiti Malaysia Pahang, 2016)
In this paper, a review on a methodology to prepared palm oil based polyurethane presented. Various methods have been attempted in the research for innovation to produce polyurethane palm oil based. Through the innovative use of palm oil in the production of polyurethane, it is expected to process an outcome that is environmentally friendly and cheaper in preparation process. Innovations that have been executed can also provide efficiency in the production of polyurethane